2023
DOI: 10.2478/acph-2023-0008
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate attenuate hyperglycemia-induced inflammatory response and renal injury in diabetic mice

Abstract: The activation of the monocyte-macrophage system and the damage to the renal and pancreatic tissue are common complications in patients with diabetes induced by hyper-glycemia. This study aimed to evaluate the effect and mechanism of butyrate (NaB), a metabolite of intestinal flora, on inhibiting the inflammatory response of human monocyte-macrophages (THP-1 cells) induced by high glucose and the damage of pancreatic and renal tissue in diabetic mice. The results showed that high concentration glucose signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Apart from the previous elaboration of protective effects of butyrate on DN, a few works explored the role of butyrate in immunity regulation [ 62 64 ]. Man Y, et al reported that sodium butyrate was capable to alleviate vacuolar degeneration of renal tubules and tubular epithelial cells exfoliation, via attenuating inflammation activation mediated by PI3K/Akt/NF-κB pathway in high glucose induced human monocyte-macrophages [ 65 , 66 ]. Butyrate could regulate Treg/Th17 equilibrium by promoting regulatory T cell differentiation while inhibiting Th17 helper T cell [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the previous elaboration of protective effects of butyrate on DN, a few works explored the role of butyrate in immunity regulation [ 62 64 ]. Man Y, et al reported that sodium butyrate was capable to alleviate vacuolar degeneration of renal tubules and tubular epithelial cells exfoliation, via attenuating inflammation activation mediated by PI3K/Akt/NF-κB pathway in high glucose induced human monocyte-macrophages [ 65 , 66 ]. Butyrate could regulate Treg/Th17 equilibrium by promoting regulatory T cell differentiation while inhibiting Th17 helper T cell [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Streptozotocin is dissolved with sodium citrate buffer (pH 4.2–45) in advance, streptozotocin solution is ready for use, and the use process is kept away from light. Each mouse was given an intraperitoneal injection of less than 1 mL [ 29 ]. The glucose concentration in the tail vein blood of the mice was measured by a blood glucose meter (Sanuo, Shanghai, China) every 5 days.…”
Section: Methodsmentioning
confidence: 99%
“…The glucose concentration in the tail vein blood of the mice was measured by a blood glucose meter (Sanuo, Shanghai, China) every 5 days. A T2DM mouse model with fasting blood glucose (FBG) higher than 11.1 mmol/L was established successfully [ 29 ]. Inulin was given to mice by intragastric administration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proir studies have demonstrated that supression of the NLRP3/Caspase-1 pathway can not only significantly inhibit the formation of fibrosis after acute kidney injury, but also induce hepatocyte pyroptosis to curb hepatocyte fibrosis [ 20 , 21 ], indicating that the NLRP3/caspase-1 axis-mediated pyroptosis is closely bound up with the process of cell fibrosis. Moreover, NaB impedes high glucose-induced NLRP3 overexpression in human monocyte macrophage THP-1 cells, negatively regulates NLRP3-mediated inflammatory signaling pathways, suppresses macrophage activation and secretion of pro-inflammatory mediators (such as IL-18 and IL-1β), reduces intestinal inflammation level, and limits colitis-associated cancer development [ 22 , 23 ]. Both the NaB signal and the GPR43 signal after binding to NaB activate NLRP3 inflammasome, and thus producing more IL-18 [ 24 ], suggesting that NaB exhibits a close association with the NLRP3 inflammasome and its mediated inflammatory pathway.…”
Section: Introductionmentioning
confidence: 99%